Global Biodiversity : Volume 1: Selected Countries in Asia - Pullaiah, T.; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
This is the first volume in the new multi-volume set, Global Biodiversity. Each volume in this series aims to provide insightful information on the biodiversity of selected nations in particular regions. The volumes summarize the available data on both wild and cultivated plants, wild and domesticated animals, and microbes of the different nations. Global Biodiversity, Volume 1: Selected Countries in Asia focuses on selected countries of Asia, providing an abundance of biodiversity information on Afghanistan, Bangladesh, India, Indonesia, Iran, Iraq, Japan, Lebanon, Malaysia, Mongolia, Myanmar, Nepal, and Vietnam. The first chapter in the volume provides an informative overview of what is biodiversity along with biogeographic classifications. It provides explanations of biodiversity patterns and species number; biodiversity conservation, protection, and international commitments and cooperation; biodiversity threats and drivers of change (such as human population growth, climate change, land use change); and the economics of biodiversity as well.
Global Biodiversity Threats and Development Trends -- Kjetil Bevanger -- Biodiversity in Afghanistan -- S. W. Breckle, I. C. Hedge, and M. D. Rafiqpoor -- Biodiversity of Bangladesh -- Sharif A. Mukul, Shekhar R. Biswas, and A. Z. M. Manzoor Rashid -- Biodiversity in India -- T. Pullaiah and Ramakrishna -- Biodiversity of Indonesia -- Irawati and Didik Widyatmoko -- Biodiversity of Iran -- M. M. Dehshiri -- Biodiversity in Iraq -- Nature Iraq -- Biodiversity of Japan -- Takafumi Ohsawa, Fumiko Nakao, and Tohru Nakashizuka -- Biodiversity in Lebanon -- Salma N. Talhouk, M. Itani, and M. Al-Zein -- Biodiversity in Malaysia -- A. Latiff -- Biodiversity in Mongolia -- Gombobaatar Sundev et al. -- Biodiversity in Myanmar -- Naing Zaw Htun -- Biodiversity of Nepal: An Overview -- Krishna K. Shrestha and Siddhartha B. Bajracharya -- Biodiversity of Vietnam -- P. K. Loc and M. D. Yen Leonid Averyanov.
Includes bibliographical references and index.
Also available in print format.
Keywords: Biodiversity -- Asia; Species diversity -- Asia; Biodiversity conservation -- Asia; Electronic books